How does CEO tenure matter? The mediating role of firm‐employee and firm‐customer relationships. (21st March 2013) - Luo, Xueming; Kanuri, Vamsi K.; Andrews, Michelle
<x xml:space="preserve">Abstract</x> While the direct influence of CEO tenure on firm performance has been examined in the strategy literature, the underlying channels of influence have remained largely unexplored. This article draws upon the career seasons paradigm, learning perspectives, and marketing literature to examine whether firm‐employee and firm‐customer relationships are the pathways through which CEO tenure influences firm performance. Results from the analysis of a large data set reveal that: (1) CEO tenure has a positive and linear association with firm‐employee relationship strength but an inverted U‐shaped association with firm‐customer relationship strength; (2) industry uncertainty intensifies these associations; and (3) firm‐employee and firm‐customer relationship strength mediate the effects of CEO tenure on firm performance. These findings have implications for a more balanced and nuanced view of CEO tenure. Copyright © 2013 John Wiley & Sons, Ltd.